Electrolyte and lithium ion battery containing same

By adding the first additive containing Si-O groups and C-N six-membered rings to the electrolyte of lithium-ion batteries, the problem of cracking/powdering caused by the volume change of the silicon anode material during the lithium insertion/delithiation process is solved, which is significant. Improved battery cycle performance and high temperature storage performance.

CN119361822AActive Publication Date: 2025-01-24EVE POWER CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411392707.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-24
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

When using silicon negative electrode material in lithium-ion batteries, volume changes during lithium-embedding/deliquefaction lead to particle cracking/powdering, affecting cycle life and high-temperature storage performance.

Method used

An electrolyte is used, which contains a first additive. The first additive contains Si-O groups and C-N six-membered rings, which can capture water, PF5, HF, etc. in the electrolyte and inhibit the impact of HF on the positive and negative electrode interfaces. It has a destructive effect and decomposes on the surface of the silicon anode to form substances with interface stabilization.

Benefits of technology

Improve the circulation performance and high temperature storage performance of lithium -ion batteries. By stabilizing the positive and negative electrode interface, the side reaction and silicon expansion are inhibited, and the battery life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361822A_ABST
    Figure CN119361822A_ABST
Patent Text Reader

Abstract

The invention specifically discloses an electrolyte and a lithium ion battery containing the electrolyte. The electrolyte comprises an organic solvent, an electrolyte lithium salt and a first additive, the structural formula of the first additive is as follows: # imgabs0, Si-O groups are introduced into the electrolyte by the first additive, and water, PF5, HF and the like in the electrolyte can be captured, so that the influence of HF on a positive and negative electrode interface is inhibited, and the stability of the positive and negative electrode interface is improved; besides, unsaturated siloxane can be preferentially decomposed into a film on the surface of the negative electrode to form a silicon-containing substance with a stable interface, so that side reaction and expansion of the silicon-containing negative electrode are inhibited, and the cycle performance and the high-temperature storage performance of the lithium ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to an electrolyte and a lithium-ion battery containing the electrolyte. Background Art

[0002] Lithium-ion batteries are one of the main energy storage technologies in the new energy market due to their high energy density, portability, strong designability and high safety. With the development of new energy technologies, the demand for high energy density lithium-ion batteries is increasing. How to improve the energy density of lithium-ion batteries has gradually become a research hotspot.

[0003] At present, the use of silicon negative electrode materials or silicon-carbon negative electrode materials is the main way to improve the energy density of lithium-ion batteries. As one of the high-capacity negative electrode materials, silicon (Si) has attracted widespread attention due to its high theoretical specific capacity of 3579mAh / g, and is expected to improve the volume energy density of lithium-ion batteries; however, Si will undergo significant volume changes during the lithium insertion / extraction process, which will cause particle cracking / powdering, affecting the cycle life and high-temperature storage performance of lithium-ion batteries; while the electrochemical kinetics of silicon-carbon materials are slow, and they will produce a large volume expansion during the lithium-ion battery cycle, and the silicon after expansion and crushing is in an inert state, which will make silicon-carbon negative electrode materials difficult to apply. Summary of the invention

[0004] In order to improve the cycle performance and high-temperature storage performance of a lithium battery using a silicon-containing negative electrode material, the present application provides an electrolyte and a lithium-ion battery containing the electrolyte.

[0005] In a first aspect, the present application provides an electrolyte, which adopts the following technical solution:

[0006] An electrolyte comprises an organic solvent, an electrolyte lithium salt and a first additive, wherein the structural formula of the first additive is as follows:

[0007]

[0008] First, the electrolyte of the present application uses a first additive, which contains a Si-O group. The Si-O group can capture water, PF5, HF, etc. in the electrolyte, thereby inhibiting the destructive effect of HF on the positive and negative electrode interfaces and improving the stability at the positive and negative electrode interfaces; in addition, unsaturated siloxanes can preferentially decompose into films on the surface of the silicon negative electrode to form silicon-containing substances with interface stabilization, inhibiting the occurrence of side reactions at the negative electrode and the expansion effect of the silicon-carbon negative electrode, thereby improving the cycle performance and high-temperature storage performance of lithium-ion batteries containing silicon negative electrodes. Second, the first additive also contains a CN hexacyclic ring. The three N atoms in the CN hexacyclic ring each have a lone pair of electrons that synergize with the carbonyl group, thereby increasing the Lewis basicity of the carbonyl group, thereby preferentially reacting with the lithium salt decomposition byproduct PF5 in the electrolyte system, thereby inhibiting the reaction between PF5 and organic solvents to prevent the organic solvents in the electrolyte system from being consumed during the lithium battery cycle. In addition, the synergy between the two can effectively enhance the complexing ability of N with the high-valent metal atoms in the positive electrode of the lithium battery, thereby effectively reducing the oxidative decomposition of the electrolyte by the positive electrode material, which helps to improve the cycle performance and high-temperature storage performance of silicon-containing negative electrode lithium batteries.

[0009] Preferably, the mass proportion of the first additive in the electrolyte is 0.5%-3%.

[0010] The second additive The mass proportion of the first additive of the present application in the electrolyte is too small, and it is impossible to generate a substance with an interface stabilizing effect on the surface of the silicon-containing negative electrode, which will affect the stability of the silicon-containing negative electrode interface. Moreover, the first additive at this time cannot cooperate with other additives to effectively alleviate the degree of reaction between the positive electrode interface and the electrolyte. Further, due to certain mutual influences between the positive and negative electrode sheets, the violent interface reaction at the negative electrode will also have a negative impact on the interface stability at the positive electrode, thereby causing the performance of the lithium-ion battery to deteriorate. The mass proportion of the first additive in the electrolyte is too large. On the one hand, it will reduce the stability of the electrolyte, which is not conducive to improving the stability at the negative electrode interface and the positive electrode interface. On the other hand, it will inhibit the performance of other types of additives, thereby having a negative impact on the performance of the electrolyte and further reducing the cycle performance of the lithium-ion battery.

[0011] Preferably, the second additive is further included, wherein the second additive includes at least one of vinyl sulfite, propylene sulfite, fluoroethylene carbonate and vinylene carbonate.

[0012] Preferably, the second additive includes fluoroethylene carbonate and vinylene carbonate.

[0013] Fluoroethylene carbonate and vinylene carbonate have a synergistic effect. By generating a SEI film that is rich in inorganic components, dense, uniform and has a certain elasticity, it reduces the reaction at the negative electrode interface and increases the ion conductivity of the SEI film, thereby improving the volume expansion problem of the silicon-containing negative electrode, and helps to improve the cycle stability and high-temperature storage performance of lithium-ion batteries containing silicon-carbon negative electrodes.

[0014] Preferably, the mass proportions of fluoroethylene carbonate and vinylene carbonate in the electrolyte are independently selected from 1.5%-3.5% and 1.5%-3.5%.

[0015] Preferably, the mass ratio of fluoroethylene carbonate to vinylene carbonate is 1-2:1-2.

[0016] By controlling the mass proportion of fluoroethylene carbonate and vinylene carbonate in the electrolyte and their mixing ratio, on the one hand, it helps to further improve the stability of the SEI film and reduce side reactions at the negative electrode interface. On the other hand, it helps to improve the stability of the electrolyte and provide a good environmental basis for the first additive to play a role in the electrolyte, thereby further improving the cycle performance of lithium-ion batteries.

[0017] Preferably, the electrolyte lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium difluorophosphate, lithium trifluoromethanesulfonate, and lithium bis(fluorosulfonyl)imide; and the mass proportion of the electrolyte lithium salt in the electrolyte is 10%-15%.

[0018] By doping the electrolyte with an appropriate type and concentration of electrolyte lithium salt, the dissolution of metal ions at the positive electrode can be inhibited, the dissolved metal ions can be prevented from damaging the SEI film, and the active lithium consumption during the lithium-ion battery cycle can be compensated, which helps to improve the cycle performance of lithium-ion batteries.

[0019] Preferably, the organic solvent comprises ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate; the mass ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 15-20:10-20:60-65.

[0020] The organic solvent of the present application is used in combination with ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, and the usage ratio of the three is controlled, which helps to improve the stability of the electrolyte, provides a stable environmental basis for the first additive and the second additive to play their respective roles and cooperate with each other, thereby improving the stability of the electrolyte and also helping to improve the cycle performance of the lithium-ion battery.

[0021] In a second aspect, the present application provides a lithium-ion battery, which adopts the following technical solution:

[0022] A lithium ion battery comprises a positive electrode sheet, a separator, a negative electrode sheet and the electrolyte as described above.

[0023] Preferably, the active material of the positive electrode sheet includes at least one of lithium iron manganese phosphate, lithium iron phosphate, and a ternary positive electrode material; the active material of the negative electrode sheet includes at least one of a pure silicon material and a silicon / carbon composite material.

[0024] Preferably, the diaphragm is a PE diaphragm. DETAILED DESCRIPTION

[0025] For better understanding and implementation, the technical solution of the present application will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0027] Unless otherwise indicated, all numerical values ​​expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.

[0028] As used herein, "and / or" means one or all of the mentioned elements.

[0029] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.

[0030] All percentages in this application are by weight unless otherwise stated.

[0031] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.

[0032] The first additive in the embodiment of the present application The CAS number is 26947-14-8.

[0033] Example 1

[0034] 1. Electrolyte and preparation of electrolyte

[0035] The electrolyte in this embodiment includes an organic solvent, an electrolyte lithium salt, a second additive, and a first additive in a mass ratio of 81%:12.5%:4%:2.5%;

[0036] The organic solvent is composed of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 20:20:60.

[0037] The electrolyte lithium salt is lithium hexafluorophosphate LiPF6,

[0038] The second additive is composed of vinylene carbonate VC and fluoroethylene carbonate FEC in a mass ratio of 1:1;

[0039] The preparation steps of the electrolyte are as follows: in an argon atmosphere, ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate are first mixed to obtain an organic solvent, a formulated amount of electrolyte lithium salt and a second additive are added to the organic solvent, and finally the first additive is added, and the electrolyte is obtained by stirring and mixing.

[0040] 2. Preparation of lithium batteries

[0041] The lithium battery of this embodiment includes a positive electrode, a negative electrode, a separator and the above-mentioned electrolyte.

[0042] Preparation of positive electrode sheet: positive electrode active material (lithium manganese iron phosphate), conductive agent (acetylene black) and binder (PVDF) are prepared into positive electrode slurry in a mass ratio of 94:3:3; the positive electrode slurry is coated on an aluminum foil current collector and vacuum dried to obtain a positive electrode sheet.

[0043] Preparation of negative electrode sheet: negative electrode active material (silicon carbon material), conductive agent (acetylene black) and binder (CMC), binder (SBR) are prepared into negative electrode slurry in a mass percentage of 94:1:2:3; the negative electrode slurry is coated on the copper foil current collector, vacuum dried to obtain a negative electrode sheet.

[0044] After assembling the above-mentioned positive electrode sheet, negative electrode sheet and PE separator to obtain a battery cell, the battery cell is transferred into a casing, and then the electrolyte prepared in this embodiment is injected, formed and constant in volume to obtain the lithium-ion battery of this embodiment.

[0045] Example 2

[0046] 1. Electrolyte and preparation of electrolyte

[0047] The electrolyte in this embodiment includes an organic solvent, an electrolyte lithium salt, a second additive and a first additive in a mass ratio of 83%:12.5%:4%:0.5%;

[0048] The organic solvent is composed of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 20:20:60.

[0049] The electrolyte lithium salt is lithium hexafluorophosphate LiPF6,

[0050] The second additive is composed of vinylene carbonate VC and fluoroethylene carbonate FEC in a mass ratio of 1:1;

[0051] The preparation steps of the electrolyte are as follows: in an argon atmosphere, ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate are first mixed to obtain an organic solvent, a formulated amount of electrolyte lithium salt and a second additive are added to the organic solvent, and finally the first additive is added, and the electrolyte is obtained by stirring and mixing.

[0052] 2. Preparation of lithium batteries

[0053] The lithium battery of this embodiment includes a positive electrode, a negative electrode, a separator and the above-mentioned electrolyte.

[0054] Preparation of positive electrode sheet: positive electrode active material (lithium manganese iron phosphate), conductive agent (acetylene black) and binder (PVDF) are prepared into positive electrode slurry in a mass ratio of 94:3:3; the positive electrode slurry is coated on an aluminum foil current collector and vacuum dried to obtain a positive electrode sheet.

[0055] Preparation of negative electrode sheet: negative electrode active material (silicon carbon material), conductive agent (acetylene black) and binder (CMC), binder (SBR) are prepared into negative electrode slurry in a mass percentage of 94:1:2:3; the negative electrode slurry is coated on the copper foil current collector, vacuum dried to obtain a negative electrode sheet.

[0056] After assembling the above-mentioned positive electrode sheet, negative electrode sheet and PE separator to obtain a battery cell, the battery cell is transferred into a casing, and then the electrolyte prepared in this embodiment is injected, formed and constant in volume to obtain the lithium-ion battery of this embodiment.

[0057] Example 3

[0058] 1. Electrolyte and preparation of electrolyte

[0059] The electrolyte in this embodiment includes an organic solvent, an electrolyte lithium salt, a second additive and a first additive in a mass ratio of 77%:15%:6%:2%;

[0060] The organic solvent is composed of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 15:20:65.

[0061] The electrolyte lithium salt is lithium hexafluorophosphate LiPF6,

[0062] The second additive is composed of ethylene sulfite ES and propylene sulfite TMS in a mass ratio of 1:1;

[0063] The preparation steps of the electrolyte are as follows: in an argon atmosphere, ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate are first mixed to obtain an organic solvent, a formulated amount of electrolyte lithium salt and a second additive are added to the organic solvent, and finally the first additive is added, and the electrolyte is obtained by stirring and mixing.

[0064] 2. Preparation of lithium batteries

[0065] The lithium battery of this embodiment includes a positive electrode, a negative electrode, a separator and the above-mentioned electrolyte.

[0066] Preparation of positive electrode sheet: positive electrode active material (lithium manganese iron phosphate), conductive agent (acetylene black) and binder (PVDF) are prepared into positive electrode slurry in a mass ratio of 94:3:3; the positive electrode slurry is coated on an aluminum foil current collector and vacuum dried to obtain a positive electrode sheet.

[0067] Preparation of negative electrode sheet: negative electrode active material (silicon carbon material), conductive agent (acetylene black) and binder (CMC), binder (SBR) are prepared into negative electrode slurry in a mass percentage of 94:1:2:3; the negative electrode slurry is coated on the copper foil current collector, vacuum dried to obtain a negative electrode sheet.

[0068] After assembling the above-mentioned positive electrode sheet, negative electrode sheet and PE separator to obtain a battery cell, the battery cell is transferred into a casing, and then the electrolyte prepared in this embodiment is injected, formed and constant in volume to obtain the lithium-ion battery of this embodiment.

[0069] Example 4

[0070] 1. Electrolyte and preparation of electrolyte

[0071] The electrolyte in this embodiment includes an organic solvent, an electrolyte lithium salt, a second additive and a first additive in a mass ratio of 86%:12%:1%:3%;

[0072] The organic solvent is composed of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 18:22:60.

[0073] The electrolyte lithium salt is lithium hexafluorophosphate LiPF6,

[0074] The second additive is composed of ethylene sulfite ES and fluoroethylene carbonate FEC in a mass ratio of 1:1;

[0075] The preparation steps of the electrolyte are as follows: in an argon atmosphere, ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate are first mixed to obtain an organic solvent, a formulated amount of electrolyte lithium salt and a second additive are added to the organic solvent, and finally the first additive is added, and the electrolyte is obtained by stirring and mixing.

[0076] 2. Preparation of lithium batteries

[0077] The lithium battery of this embodiment includes a positive electrode, a negative electrode, a separator and the above-mentioned electrolyte.

[0078] Preparation of positive electrode sheet: positive electrode active material (lithium manganese iron phosphate), conductive agent (acetylene black) and binder (PVDF) are prepared into positive electrode slurry in a mass ratio of 94:3:3; the positive electrode slurry is coated on an aluminum foil current collector and vacuum dried to obtain a positive electrode sheet.

[0079] Preparation of negative electrode sheet: negative electrode active material (silicon carbon material), conductive agent (acetylene black) and binder (CMC), binder (SBR) are prepared into negative electrode slurry in a mass percentage of 94:1:2:3; the negative electrode slurry is coated on the copper foil current collector, vacuum dried to obtain a negative electrode sheet.

[0080] After assembling the above-mentioned positive electrode sheet, negative electrode sheet and PE separator to obtain a battery cell, the battery cell is transferred into a casing, and then the electrolyte prepared in this embodiment is injected, formed and constant in volume to obtain the lithium-ion battery of this embodiment.

[0081] Example 5

[0082] 1. Electrolyte and preparation of electrolyte

[0083] The electrolyte in this embodiment is the same as that in Embodiment 1 in that the mass fraction of the first additive in the electrolyte is adjusted to 0.1%, and the portion of the electrolyte less than 100% can be obtained by adaptively adjusting the amount of the organic solvent (one or more of the organic solvents can be adjusted). Other steps and parameter settings are the same as those in Embodiment 1.

[0084] 2. Preparation of lithium batteries

[0085] The preparation of lithium battery is consistent with that in Example 1.

[0086] Example 6

[0087] 1. Electrolyte and preparation of electrolyte

[0088] The electrolyte in this embodiment is different from the electrolyte in Embodiment 1 in that the mass fraction of the first additive in the electrolyte is adjusted to 4%, and the portion of the electrolyte that is less than 100% can be obtained by adaptively adjusting the amount of the organic solvent (one or more of the organic solvents can be adjusted). Other steps and parameter settings are consistent with Embodiment 1.

[0089] 2. Preparation of lithium batteries

[0090] The preparation of lithium battery is consistent with that in Example 1.

[0091] Example 7

[0092] 1. Electrolyte and preparation of electrolyte

[0093] The electrolyte in this embodiment is different from the electrolyte in Embodiment 1 in that the second additive is composed of vinylene carbonate VC and fluoroethylene carbonate FEC in a mass ratio of 1:2. Other steps and parameter settings are consistent with those in Embodiment 1.

[0094] 2. Preparation of lithium batteries

[0095] The preparation of lithium battery is consistent with that in Example 1.

[0096] Example 8

[0097] 1. Electrolyte and preparation of electrolyte

[0098] The electrolyte in this embodiment is different from the electrolyte in Embodiment 1 in that the second additive is composed of vinylene carbonate VC and fluoroethylene carbonate FEC in a mass ratio of 2:1. Other steps and parameter settings are consistent with those in Embodiment 1.

[0099] 2. Preparation of lithium batteries

[0100] The preparation of lithium battery is consistent with that in Example 1.

[0101] Example 9

[0102] 1. Electrolyte and preparation of electrolyte

[0103] The electrolyte in this embodiment is different from the electrolyte in Embodiment 1 in that the second additive is composed of vinylene carbonate VC and fluoroethylene carbonate FEC in a mass ratio of 1:7. Other steps and parameter settings are consistent with those in Embodiment 1.

[0104] 2. Preparation of lithium batteries

[0105] The preparation of lithium battery is consistent with that in Example 1.

[0106] Example 10

[0107] 1. Electrolyte and preparation of electrolyte

[0108] The electrolyte in this embodiment is different from the electrolyte in Embodiment 1 in that the second additive is composed of vinylene carbonate VC and fluoroethylene carbonate FEC in a mass ratio of 7:1. Other steps and parameter settings are consistent with those in Embodiment 1.

[0109] 2. Preparation of lithium batteries

[0110] The preparation of lithium battery is consistent with that in Example 1.

[0111] Embodiment 11

[0112] 1. Electrolyte and preparation of electrolyte

[0113] The electrolyte in this embodiment is different from the electrolyte in Embodiment 1 in that the second additive is composed of vinylene carbonate VC and vinyl sulfate DTD in a mass ratio of 1:1. Other steps and parameter settings are consistent with those in Embodiment 1.

[0114] 2. Preparation of lithium batteries

[0115] The preparation of lithium battery is consistent with that in Example 1.

[0116] Example 12

[0117] 1. Electrolyte and preparation of electrolyte

[0118] The electrolyte in this embodiment is different from the electrolyte in Embodiment 1 in that the second additive is composed of vinyl sulfate DTD and fluoroethylene carbonate FEC in a mass ratio of 1:1. Other steps and parameter settings are consistent with those in Embodiment 1.

[0119] 2. Preparation of lithium batteries

[0120] The preparation of lithium battery is consistent with that in Example 1.

[0121] Example 13

[0122] 1. Electrolyte and preparation of electrolyte

[0123] The electrolyte in this embodiment is the same as that in the embodiment 1 in that the second additive is composed of vinylene carbonate VC. The other steps and parameter settings are the same as those in the embodiment 1.

[0124] 2. Preparation of lithium batteries

[0125] The preparation of lithium battery is consistent with that in Example 1.

[0126] Embodiment 14

[0127] 1. Electrolyte and preparation of electrolyte

[0128] The electrolyte in this embodiment is the same as that in the embodiment 1 in that the second additive is composed of fluoroethylene carbonate FEC. The other steps and parameter settings are the same as those in the embodiment 1.

[0129] 2. Preparation of lithium batteries

[0130] The preparation of lithium battery is consistent with that in Example 1.

[0131] Comparative Example 1

[0132] 1. Electrolyte and preparation of electrolyte

[0133] The electrolyte in this comparative example is different from that in Example 1 in that the electrolyte does not contain the first additive, and the electrolyte less than 100% can be obtained by adaptively adjusting the amount of the organic solvent (one or more of the organic solvents can be adjusted). Other steps and parameter settings are consistent with those in Example 1.

[0134] 2. Preparation of lithium batteries

[0135] The preparation of lithium battery is consistent with that in Example 1.

[0136] Comparative Example 2

[0137] 1. Electrolyte and preparation of electrolyte

[0138] The electrolyte in this comparative example is different from that in Example 1 in that the electrolyte does not contain the second additive, and the electrolyte less than 100% can be obtained by adaptively adjusting the amount of organic solvent (one or more of the organic solvents can be adjusted). Other steps and parameter settings are consistent with those in Example 1.

[0139] 2. Preparation of lithium batteries

[0140] The preparation of lithium battery is consistent with that in Example 1.

[0141] Test Method

[0142] 1. Lithium-ion battery cycle performance test

[0143] Charge at 1C constant current at 25℃ to a voltage of 4.5V, then charge at 4.5V constant voltage to a current ≤0.05C, stand for 10min, and then discharge at 1C constant current to a cut-off voltage of 2.5V. The above is one charge and discharge cycle. The lithium-ion battery was charged and discharged 1000 times at 25℃ under the above conditions, and the cycle capacity retention rate of the lithium-ion battery was calculated and recorded in Table 1.

[0144] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.

[0145] 2. High temperature storage performance test of lithium-ion batteries

[0146] The lithium-ion battery was charged to 4.5V at 1C constant current and constant voltage at 25℃, left to stand for 5min, and then discharged to 2.5V at 0.1C, and the discharged capacity was recorded as the initial capacity; then charged to 4.5V at 1C constant current and constant voltage, and the initial thickness of the battery cell and the initial internal resistance of the lithium-ion battery were measured, and then the lithium-ion battery was stored at 60℃±2℃. After open circuit storage for 30d, the lithium-ion battery was taken out and the hot thickness was tested. After standing at room temperature for 2h, the internal resistance after storage was tested, and then the battery cell was charged and discharged at 1C to test the remaining capacity and recovery capacity; the thermal thickness change rate, internal resistance change rate, capacity retention rate, and capacity recovery rate were calculated, and the data were recorded in Table 1.

[0147] Thermal thickness change rate (%) = (hot thickness - initial thickness) / initial thickness × 100%;

[0148] Internal resistance change rate (%) = (internal resistance after storage - initial internal resistance) / initial internal resistance × 100%;

[0149] Capacity retention rate (%) = (remaining capacity / initial capacity) × 100%;

[0150] Capacity recovery rate (%) = (recovered capacity / initial capacity) × 100%.

[0151] Table 1

[0152]

[0153]

[0154] In combination with Examples 1-4, Comparative Example 1 and Table 1, it can be seen that after the first additive of the present application is added to the electrolyte, the high temperature storage performance and cycle performance of the lithium ion battery are significantly improved; this is because the Si-O group can capture HF in the electrolyte, avoiding the negative impact of HF on the positive and negative electrode interfaces, and the unsaturated siloxane can decompose at the negative electrode surface to generate substances that improve the stability of the SEI film, effectively inhibiting silicon expansion. In addition, the three N atoms in the CN six-membered ring in the first additive synergize with the carbonyl group and preferentially react with the lithium salt decomposition byproduct PF5 in the electrolyte system, thereby avoiding the PF5 reaction consuming the organic solvent in the electrolyte; in addition, it can also effectively improve the complexing ability of N with the high-valent metal atoms of the positive electrode in the lithium battery, avoiding the oxidative decomposition of the electrolyte by the positive electrode material; this is helpful to improve the cycle performance of the silicon-containing negative electrode lithium battery, thereby significantly improving the high temperature storage performance and cycle performance of the lithium ion battery.

[0155] In combination with Examples 1-6 and Table 1, it can be seen that when the mass proportion of the first additive in the electrolyte is too small (Example 5), the SEI film formed at the negative electrode is unstable, the side reaction cannot be effectively reduced, and the cycle performance and high temperature storage performance of the lithium battery are reduced; when the mass proportion of the first additive in the electrolyte is too large (Example 6), the interface stability at the positive electrode and the negative electrode deteriorates, which is not conducive to the cooperation with other additives, and the cycle performance and high temperature storage performance of the lithium battery are reduced; and when the mass proportion of the first additive in the electrolyte is 2.5%, the cycle performance and high temperature storage performance of the lithium-ion battery are better.

[0156] In combination with Example 1, Examples 7-10 and Table 1, it can be seen that by adjusting the mass proportion of vinylene carbonate VC and fluoroethylene carbonate FEC in the second additive to meet the above-mentioned ratio limit, it is beneficial to achieve the coordination effect of the two to the greatest extent, while ensuring a high content of inorganic components in the SEI film and having good ion conductivity, which helps to improve the cycle performance and high temperature storage performance of lithium-ion batteries.

[0157] In combination with Example 1, Examples 11-14 and Table 1, it can be seen that in the present application, by using vinylene carbonate VC and fluoroethylene carbonate FEC as components of the second additive, a dense, uniform and stable SEI film can be generated at the negative electrode interface, which helps to alleviate the expansion of the silicon negative electrode, so as to improve the cycle performance and high temperature storage performance of the lithium battery.

[0158] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.

Claims

1. An electrolyte, characterized in that: It includes an organic solvent, an electrolyte lithium salt and a first additive, wherein the structural formula of the first additive is as follows:

2. The electrolyte according to claim 1, characterized in that: The mass proportion of the first additive in the electrolyte is 0.5%-3%.

3. The electrolyte according to any one of claims 1 to 2, characterized in that: The invention also includes a second additive, wherein the second additive includes at least one of vinyl sulfite, propylene sulfite, fluoroethylene carbonate, and vinylene carbonate.

4. The electrolyte according to claim 3, characterized in that: The second additive includes fluoroethylene carbonate and vinylene carbonate.

5. The electrolyte according to claim 4, characterized in that: The mass proportions of fluoroethylene carbonate and vinylene carbonate in the electrolyte are independently selected from 1.5% to 3.5%.

6. The electrolyte according to claim 4, characterized in that: The mass ratio of fluoroethylene carbonate to vinylene carbonate is 1-2:1-2.

7. The electrolyte according to claim 1, characterized in that: The electrolyte lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium difluorophosphate, lithium trifluoromethanesulfonate, and lithium bis(fluorosulfonyl)imide; The electrolyte lithium salt accounts for 10%-15% by mass in the electrolyte.

8. The electrolyte according to claim 1, characterized in that: The organic solvent includes ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate; The mass ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 15-20:10-20:60-65.

9. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte as claimed in any one of claims 1 to 8.

10. The lithium-ion battery according to claim 9, characterized in that: The active material of the positive electrode sheet includes at least one of lithium iron manganese phosphate, lithium iron phosphate, and a ternary positive electrode material; the active material of the negative electrode sheet includes at least one of a pure silicon material and a silicon / carbon composite material.

Citation Information

Patent Citations

  • Lithium ion battery electrolyte and application thereof

    CN116487697A

  • Electrolyte additive, electrolyte and lithium ion battery

    CN116979144A

  • Curable silicone rubber composition and semiconductor device

    US20060270792A1